Human amniotic fluid stem cells can alleviate detrusor dysfunction caused by bladder outlet obstruction in rats - Ching-Chung Liang; Wen-Chu Huang; Steven W. Shaw; Yung-Hsin Huang; Tsong-Hai Lee (Scientific Reports, 2022)
Abstract The present study examined whether bladder detrusor dysfunction due to partial bladder outlet obstruction (pBOO) could be improved after the treatment of human amniotic fluid stem cells (hAFSCs). 72 female rats were grouped into sham operation, pBOO, and pBOO with hAFSCs treatment (pBOO + hAFSCs) for in vitro and in vivo studies. Bladder weight, bladder wall thickness, the ratio of collagen to smooth muscle and the levels of positive CD11b/c and HIS48 cells was significantly increased after pBOO but improved after hAFSCs treatment. Cystometries showed impaired bladder function after pBOO. Protein and mRNA levels of hypoxia inducible factor-1α, CCL2, interleukin-1β, transforming growth factor-β1 (TGF-β1), connective tissue growth factor (CTGF), α-smooth muscle actin, collagen I and collagen III were increased at 2 and/or 6 weeks, but proteins and mRNA expressions of protein gene product 9.5 were decreased at 2 and 6 weeks after pBOO. These abnormalities were improved after hAFSCs treatment. The expressions of TGF-β1 and CTGF in cultured detrusor cells of pBOO rats were increased but were improved after hAFSCs treatment. The present results showed hAFSCs treatment could improve bladder detrusor dysfunction in pBOO rats, which may be related to the reduction of inflammatory and pro-fibrotic markers in detrusor muscle cells.